Impact of metacognitive Awareness, self-efficacy and Locus of control on academic Performance of senior Secondary school students in Ibadan (2015)
"The study examined the impact of metacognitive awareness, self-efficacy and locus of control on academic performance of Senior Secondary School students in Ibadan. Descriptive survey research design was adopted for this study. A multi-stage random sampling technique was employed in selecting 420 participants from 12 secondary schools in Ibadan for the study. Their ages ranged between 12 years and 18 years with the mean age of 12.6 years and the standard deviation of 1.15. Three valid and reliable instruments were used to assess metacognitive awareness, academic self-efficacy and locus of control while achievement tests on English Language and Mathematics were used as a measure of academic performance of the participants. Multiple regression was used to analyse the data. The results revealed that metacognitive awareness, academic self-efficacy and locus of control were potent predictors mildly associated with academic performance. The study has implications for teachers, counsellors and educational psychologists to appropriate counselling intervention programmes and enabling environment. By so doing, the academic performance of the students could be improved barring all other teaching-learning obstacles "